2017
DOI: 10.5005/jp-journals-10050-10077
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Profile in Liver Diseases: A Study of 300 Cases in a Tertiary Care Hospital in Uttarakhand, India

Abstract: Background:The liver is the cornerstone of the coagulation system. The physiology of blood coagulation is closely linked to liver function as the liver synthesizes most of the factors of the coagulation cascade and fibrinolytic proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…Similar findings were observed by Bhatia et al [1] and Shah and Jansari et al [2] study. In the present study, male preponderance was observed in cases of liver diseases; similar findings were observed in other studies as by Tarun Kotadiya et al [3] and Bhatia et al [1] 225 patients of various liver diseases with various clinical manifestations were studied for coagulation abnormalities by doing coagulation tests like, Prothrombin time and Activated partial thromboplastin time. 25 normal individuals were included as controls.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar findings were observed by Bhatia et al [1] and Shah and Jansari et al [2] study. In the present study, male preponderance was observed in cases of liver diseases; similar findings were observed in other studies as by Tarun Kotadiya et al [3] and Bhatia et al [1] 225 patients of various liver diseases with various clinical manifestations were studied for coagulation abnormalities by doing coagulation tests like, Prothrombin time and Activated partial thromboplastin time. 25 normal individuals were included as controls.…”
Section: Discussionsupporting
confidence: 91%
“…Table 6 shows prolonged APTT in 25.9% cases of other liver diseases, 25.3% cases of Hepatitis, and 46.2% cases of Cirrhosis. Similar findings were seen in studies by Tarun Kotadiya 3 and Bhatia et al [1] . [11] 66.6 1962…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations